2017
DOI: 10.1177/0306624x17730617
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Offenders Formerly Labeled as Not Criminally Responsible: Uncovering the Ambiguity From First-Person Narratives

Abstract: The recovery paradigm is a widely accepted strength-based approach in general mental health care. Particular challenges arise when applying this paradigm in a forensic context. To address these issues, the present study examined recovery based on first-person narratives of offenders formerly labeled as not criminally responsible of whom the judicial measure was abrogated. Eleven in-depth interviews were conducted to obtain information on lived experiences and recovery resources of this hard-to-reach and unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 68 publications
(97 reference statements)
0
51
0
Order By: Relevance
“…The inclusion criteria were based on the rationale that MFG therapy is an effective treatment for families living with patients with bipolar and psychotic disorders (Asen, ; McFarlane, ). Further, we have focused on this patient population because these patients, until a recent change in the law, were often placed under an internment measure after conducting minor ‘public’ offences, particularly when they had a long psychiatric history of non‐treatment compliance (Aga et al., ; Vandevelde et al., ). The current living and treatment conditions of the mentally ill relative, the familial background, and the nature of the criminal offence played no role in the selection of the family members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were based on the rationale that MFG therapy is an effective treatment for families living with patients with bipolar and psychotic disorders (Asen, ; McFarlane, ). Further, we have focused on this patient population because these patients, until a recent change in the law, were often placed under an internment measure after conducting minor ‘public’ offences, particularly when they had a long psychiatric history of non‐treatment compliance (Aga et al., ; Vandevelde et al., ). The current living and treatment conditions of the mentally ill relative, the familial background, and the nature of the criminal offence played no role in the selection of the family members.…”
Section: Methodsmentioning
confidence: 99%
“…Family members of mentally ill offenders experience a range of emotional, financial, and psychological burdens and a double stigma, because their relative is not only seen as a psychiatric patient but also as a criminal (MacInnes & Watson, ; Rowaert et al., ; Tsang, Pearson, & Yuen, ). This is further aggravated by the fact that, until recently, mentally ill offenders – even when they only committed a minor offence – have often been incarcerated in correctional settings (e.g., prison), because of a lack of sufficient treatment facilities in (forensic) psychiatric settings (Abracen, Gallo, Looman, & Goodwill, ; Aga et al., ; Sheehy et al., ; Vandevelde et al., ). As a result, family members often become even more socially isolated, with little or no support from family, friends, or professionals (Nordström, Kullgren, & Dahlgren, ; Ridley et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to listen and to acknowledge someone by listening to what the other (i.e., the patient) has to say as a subject-contributing to a feeling of being understood and therefore acknowledged (Dahlberg & Ekman, 2017;H€ orberg, 2015). Patients cared for in a forensic psychiatric setting describe needs of feeling a sense of belonging in order to being able to be themselves and to feel being accepted (Aga, Vander Laenen, Vandevelde, Vermeersch, & Vanderplasschen, 2017). Koskinen and Lindstr€ om (2015) assert that a carer who listens, shows compassion and is together with the patient in his/her struggle in suffering can take the patient out of his/her loneliness and thus alleviate suffering.…”
Section: Forensic Psychiatric Care and Caringmentioning
confidence: 99%
“…The study emphasised the importance of being involved as a patient and that good communication between caregiver and patient is fundamental to impact care and exert influence (Selvin, Almqvist, Kjellin, & Schr€ oder, 2016). Another study showed that patients' needs of being accepted and belonging were critical for their ability to be themselves (Aga, Vander Laenen, Vandevelde, Vermeersch, & Vanderplasschen, 2017). Participation in forensic psychiatric care is complex due to its corrective and disciplinary nature.…”
Section: Introductionmentioning
confidence: 99%